Effect of micro silica and aggregate size on cracking of self-compacting concrete. Issue 1 (15th February 2019) - Sankar, Aswathy S.; Hari, Rahesh; Mini, K. M.
Abstract : In the evaluation of long-term serviceability leading to prevention of damage of self-compacting concrete (SCC) structures, a thorough understanding on fracture parameters and cracking performance from initial stage to hardened stage is important. This paper reports the effect of coarse aggregate size and micro silica addition on fracture characteristics and ductility of SCC. Experiments were performed by conducting three-point bending tests on notched beams as per recommendations by Rilem standards. For all mixes, the parameters are analysed by the size-effect method. The tests proved that an increase in the size of the coarse aggregates can increase the fracture energy and ductility due to changing fractal dimensions and the fracture process zone length. A 10% addition of micro silica showed better fracture properties. Equations for assessing the fracture energy and length of the fracture process zone using a statistical approach were then developed.